Influence of antenatal macro-nutrient and food group intakes on small for gestational age babies in South Indian women - Kurpad, A.; Thomas, T.; Soares, Mario; Dwarkanath, P (Thai Journal of Clinical Nutrition, 2011)
Background: The incidence of small for gestational age babies (SGA) is high in India (~30 %). The cause of SGA is multi-factorial, with a number of nutrients having a critical role. While maternal energy and protein have been a focus of attention, intakes of certain food groups have also shown to be related to birthweight. Objective: To uncover relationships of macronutrients and food group intakes with SGA in Indian pregnant women. Design: A cohort of 637 singleton pregnant women was studied at each trimester until delivery. Dietary and food group intake was measured by a 3-month food frequency questionnaire and maternal anthropometry recorded at each trimester. Birth outcome was recorded at hospital delivery. Results: The mean energy, protein, fat intakes were 2111kcal/d, 61.4, 56.9g/d, with median intake of cereals, fish, eggs and milk products as 256.2, 1.61, 10.5, 268.1g/d during pregnancy. The pregnant women met the protein requirements in the 1st and were close to the 2nd trimester requirements. The mean birthweight was 2.8kg and 28.8% of the babies were born SGA. Mother's of SGA babies weighed less as compared to the mother's of non SGA babies in all 3 trimesters. They also had significantly lower energy adjusted protein and fat intakes in the 2nd trimester and had low intakes of milk products and cereal by ~71 and 28 g/d. A logistic regression model adjusting for maternal and antenatal factors in the 2nd trimester, showed that mother's in the lowest tertile of protein intake had 3.06 times (95% CI: 1.51, 6.22) higher risk of developing a SGA baby.Conclusion: Our findings confirm that protein and fat intakes during 2nd trimester are significant determinants of SGA. Importantly, the data suggest that a renewed focus on improving milk and cereal intake would assist public health nutrition measures in combating this serious issue.